Kajian Ukuran Rajungan (Portunus pelagicus) Menurut Jenis Kelamin, Tingkat Kematangan Gonad dan Faktor Kondisi di Perairan Pulau Baai Bengkulu - Maylandia, Chantika Rachma; Matondang, Dina Ratnasari; Ilhami, Sitti Alya; Parapat, Andreas Jorghy; Bakhtiar, Deddy (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2021)
The resources of the blue swim crab are currently under pressure on survival due to the increasing effort to catch in nature. Management of blue swim crab resources requires information on the biological conditions of the crab to determine the size, sex, and number that can be caught. This study aims to analyze the structure of carapace width concerning differences in sex, gonad maturity level, and crab condition factors. The method used is the method of observation by measuring the length, weight, and maturity level of the gonads and then analyzed descriptively. The results showed that the size of the crabs was included in the category of juvenile to adult crabs for both male and female crabs. The growth pattern of male crabs with a coefficient of b value of 2.47 and female crabs of 2.78 shows that the growth patterns of crabs in Pulau Baai waters are negative allometric. Most of the female crabs are in the immature stage of the gonads, so the condition factor for the female crabs tends to be lower than the male crabs, this is because most of the female crabs have just passed the spawning phase.